(untitled) (Journal of Global Accounting, 2023)
This study was carried out to explore the effect of board diligence on corporate performance of quoted non-financial companies in Sub-Saharan Africa. Specifically, the it determined the effect of board expertise on corporate performance of quoted non-financial companies in Sub-Saharan Africa. It further evaluated the relationship between board diligence and corporate performance of quoted non-financial companies in Sub-Saharan Africa. It also examined the association between board gender diversity and corporate performance of quoted non-financial companies in Sub-Saharan Africa. The study was anchored on the agency theory collected data from annual reports of quoted non-financial companies in Sub-Saharan Africa. Panel regression analysis was used to verify whether the studied variables impact on the corporate financial performance of quoted non-financial companies in Sub-Saharan Africa. Findings of the study showed a positive and significant effect of board expertise and board diligence on corporate financial performance; and a negative association between gender diversity and corporate financial performance. The study therefore concludes that board diligence influences the corporate financial performance of quoted non-financial firms in Sub-Saharan Africa, and recommends amongst others that regulatory institutions in Sub-Saharan Africa should enforce attendance to board meetings by board members.